On the Stability of Underground Masonry Vaults: The Case of the Mairie d'Ivry Station of the Paris Metro. Issue 1 (2nd January 2023) - Moreno Regan, O.; Bourgeois, E.; Douroux, J.F.
ABSTRACT: An analysis is presented to study the stability of a shallow masonry tunnel of the Paris metro subjected to the spreading of the vault's supports caused by nearby excavations. FEM numerical computations are carried out using a specifically developed model for the masonry that combines a homogenization technique with a damage model. Calculations display three hinges in the vault. Measures show that the masonry vault may withstand about 2 centimeters of support spreading. Soil–structure interaction analysis shows that the ground reaction is critical to ensure stability. The loss of stiffness and shear strength of the soil next to the sidewalls produces severe deformations and cracks in the structure. Based on the results some thresholds are proposed. The study also presents an analysis on the importance of the constitutive law for masonry and a brief discussion on the use of Eurocodes to investigate the stability of the vault.